Early feeding profiles based on breastfeeding, infant formula and introduction of solid foods. (13th November 2019) - Amazouz, H; Bougas, N; de Lauzon-Guillain, B; Momas, I; Rancière, F
Abstract: Background: As early feeding practices may be related with allergy at older age, we aimed to investigate infant-feeding profiles in the first year of life and their determinants in the PARIS (Pollution and Asthma Risk: an Infant Study) cohort. Methods: This study included 3446 infants. Feeding data was collected using standardized questionnaires at 1, 3, 6, 9 and 12 months. At each time, we considered 6 variables such as (i) breastfeeding (no, mixed, exclusive), consumption of formula (no, yes): (ii) regular formula, (iii) hypoallergenic, (iv) with pre-/probiotics, or (v) extensively hydrolyzed/soya, as well as (vi) solid foods introduction (no, yes: 0, 1, ≥2 allergenic foods). Children with similar feeding profiles over the first year of life were grouped together using multidimensional longitudinal cluster analysis. Socio-demographic and health determinants of these profiles were examined using multinomial logistic regression models. Results: Five distinct profiles were identified. Profile 1 (45%) included children mainly fed with regular formula. Children from Profile 2 (27%) were exclusively breastfed during the first 3 months. Children from the other three profiles were moderately breastfed and differed regarding the type of formula consumed: pre-/probiotics for Profile 3 (17%), hypoallergenic for Profile 4 (7%), or extensively hydrolyzed/soya for Profile 5 (4%). Profiles did not seem to differ regarding timing of solid foods introduction, except Profile 5 starting later. Compared to Profile 1, children from Profiles 2 to 5 were more likely to have parental history of allergy and higher family socioeconomic status (SES). Profile 5 appeared to be influenced by early health outcomes such as eczema or food reactions. Conclusions: We identified different early feeding profiles. Parental history of allergy, SES and early health outcomes seem to be important determinants of these profiles. Associations of these profiles with the development of allergic disease will be studied. Key messages: These results are important to better understand early-life feeding practices and their contributors. Their possible role in helping to prevent allergic diseases in later life will be further studied.